Standar Mutu Pendidikan Al-Qur'an - Dinda Zulaikha; Pilma Sindy Arizka; Ahmad Darlis; Winda Nurul Azizah; Chici Paramitha Harahap (Departement of Mathematics Education, 2023)
At all times, the issue of the quality of Indonesian education (including Indonesian Islamic education) has always been hotly discussed. Institutions can be called quality in the TQM concept must meet predetermined specifications. Operationally, quality is determined by two factors, namely the fulfillment of predetermined specifications which is called quality in fact (actual quality) and the fulfillment of the expected specifications according to the demands and needs of service users which is called quality in perception (perception quality). One of the efforts to maintain the quality of Al-Qur'an Education must be a clear and standardized curriculum. This article aims to find out the Al-Quran quality education standards and the process of Al-Qur'an education. In presenting the results of the research, the authors used qualitative methods with a library research approach by reading or studying books on quality standards for the education of the Koran, journals, articles, and reports on relevant previous research results. PQ quality standards can be achieved if all components of Al-Qur'an education also meet the standards.